Evaluation of phytochemicals and essential oils of Cupressus semprevirens in controlling cattle tick Rhipicephalus annulatus (Acari: Ixodidae) - Mai Ahmed Taha; Asmaa Ali Baioumy Ali (BMC Plant Biology)
Abstract Background Cupressus sempervirens is one of the conifer plants, that is used as an antimicrobial, antioxidant, anthelminthic, and many other health purposes. Rhipicephalus annulatus is one of the hard tick genera affecting the production and health of domestic animals in Egypt. Extensive use of chemical acaricides in the management of ticks caused acaricide resistance, environmental contamination, residues in meat and milk, and harmful effects on non-target species. For these reasons, there is an urgent need to create efficient, environmentally friendly acaricides. This work aimed to assay the essential oils and establish the phytochemical analysis of C. sempervirens extract, its effects against the semi-engorged females of R. annulatus, and discuss their possible control effects. Results Using the spray-dip method by C. sempervirens ethanol, methanol, distal water, and chloroform extracts at different concentrations (10–50%), revealed a decrease in the percentage of mobile female R. annulatius ticks, and increased mortality proportionally with days after treatments (14 days) and/or extract concentrations (10–50%). The ethanol extracts showed their strongest acaricidal effect, where the female mortality percentage reached 100% using all concentrations at the end of the examined period. In addition, the estimated LC50 and LC95 of C. sempervirens ethanolic extract were recorded as the lowest values (12.2% and 17%, respectively) after 14 days of treatment compared with other extract types. The 50% ethanolic extract of C. sempervirens (the most effective one) revealed the presence of bioactive metabolites i.e. flavonoids, tannins, and carbohydrates (TSS). Also, its total antioxidant capacity and potential free-radical activity (DPPH) were estimated. Using GC-MS, the extracted oil revealed the presence of four major compounds i.e., Eicosapentaenoic acid (50.85%), 10,12-Docosadiynedioic acid (27.58%),10-Undecynoic acid (14.28%) and Palmitic acid (5.42%). The efficiency of all phytochemicals and essential oils was discussed in the current study. Conclusion The phytochemicals and essential oils found in C. sempervirens could enhance our understanding and help in developing potential strategies for controlling ticks in general and for R. annulatus, in particular, using environmentally friendly agents.